Consci??ncia e comportamento ambiental de consumidores na escolha do combust??vel - Tavares, Jefferson Santos (2018)
With the population growth of the last decades, there is an increase in anthropic activities, a term that is used in ecology to define everything that results from human action in the environment. The human being who is the cause of the degradation of the environment in which he lives, is also the main harmed. Deforestation, for example, endangers several ecosystems. Despite that some activities deplete natural resources, alter the climate, and pollute the environment, compromise groundwater and biodiversity. Issues surrounding global warming are increasingly on the agenda and mitigating measures are proposed to maintain a favorable environment for future generations. This work brings the results of a study the objective was to identify the relationship of consciousness and environmental behavior of consumers in the choice of fuel. The theoretical reference was limited to a bibliographical survey of articles, dissertations and theses on the subject that addresses habits linked to consumption, through the power of choice of consumers. Official data shows the growing demand for flex-fuel vehicles in the country, consumer behavior, and factors that influence their choice for products that are less aggressive to the environment, in this case, ethanol. It is a quantitative research, and the data collection was done through a questionnaire made available on the Internet, answered by fuel consumers. The results indicate that socioeconomic factors have no direct impact on fuel consumption and that individuals with higher levels of environmental behavior measured by the ECCB scale tend to choose ethanol as fuel to fuel their vehicles. It is concluded that the fact that an individual is environmentally aware is not a guarantee of environmental behavior, although he is aware of the impacts of his choices, consumers still need some stimulus to make pro-environmental consumption habits routine.